Synthesis of transparent dispersion of monodispersed silver nanoparticles with excellent conductive performance using high-gravity technology - Han, X.; Zeng, X.; Zhang, J.; Huan, H.; Wang, J.; Foster, Neil; Chen, J. (Elsevier BV, 2016)
© 2016 Elsevier B.V. Transparent dispersion of silver nanoparticles (Ag-NPs) is important for transparent conductive coatings to fabricate the printed electronic devices such as flexible displays and solar cells. However, it is still great challenge to produce the transparent dispersion of Ag-NPs in large scale. In this work, we synthesize the transparent dispersion of monodispersed Ag-NPs with excellent conductive performance by a high-gravity strategy using rotating packed bed (RPB) reactor, which is easy to realize the large scale production. Based on the nano-dispersion, the transparent conductive films are further fabricated. The as-synthesized Ag-NPs are monodispersed in liquid medium with the average diameter about 7 nm. Compared with stirred tank reactor (STR), the Ag-NPs in transparent dispersions prepared by RPB have a smaller average diameter, a narrower particle size distribution (PSD) and better stability. The transparent conductive films with continuous percolated network structure exhibit excellent transparency and conductive properties. The visible transmittance of the films with a sheet resistance of 98.1 O/? and 12.7 O/? can reach 91% and 85% respectively. It is expected that the high-gravity technology would provide a promising strategy for the large-scale preparation of transparent silver dispersion for fabricating transparent electric devices.